Using information technology in the construction of the training process for wrestlers - Kerimov, F.; Bakiev, Z.; Ishmukhamedov, T. (International Journal of Wrestling Science, 2013)
INTRODUCTION In recent years, we are witnessing the fact that computer technology has been introduced into various sectors of the economy, as well as in the areas of physical culture and sport. Today, it is obvious, that it is necessary to use new information technologies for building the training process of athletes at all stages of long-term training [1,2,3]. But in the realm of sports, including wrestling, there still has not been automated system developed which allow for the construct competent training process of wrestlers. When planning the training process of wrestlers, one looks first for a system of plans designed for different periods, which must be implemented by a set of interrelated aims. While creating workout plans one needs to know the baseline of the object planning and possible prospects for change: near, medium and long-range. In the monitoring of the training process it is advisable to keep records of all factors associated with the preparedness of wrestlers, to assess their dynamics and efficiency, as well as their applications in structural formations of the training process. In the course of solving the above problems a large amount of information of various kinds is used, and the manual processing is a very time consuming process. Therefore the creation of an automated system for planning and monitoring the training process based on the use of computer technology is essential. Aim of investigation: is to create an automated system for planning and monitoring the training process of wrestlers, based on the use of computer technology. To solve this problem all of the training tools used in wrestling were divided into blocks of exercises that share similar content. Various kinds of training share specific loads which allowed one to classify the structure of the most commonly used training exercises. From training exercises we formed a compendium, training sessions, days, and weeks of complex micro-cycles and primary orientation. From various types of training tasks were formed structure of the basic and additional training sessions and complex orientation. Orientation of training sessions include the following objectives: 1) Development of a general or special explosive power 2) Development of general or special speed abilities, strength endurance, aerobic capacity; 3) Improvement of the basic techniques in combined (aerobic-alactic), (anaerobic-alactic) and (anaerobic glycolytic) directional modes of loads; 4) Increase the level of competitive activity and the technical and tactical skills of wrestlers; 5) Control the level of competitive activity and the technical and tactical skills of wrestlers; 6) The development of absolute general and special power abilities; 7) Remedial training sessions; Then, the plans for the loads of training days, weeks and stages of preparation of the annual cycle were made. Compiling plans of training structures are produced in an automated way by computer. The above plans provide notes attached to the calendar dates of the annual cycle. CONCLUSIONS The accumulated allowance of all structures of the training process, which allows an analysis of the parameters of the current and staged control improve managing of training process. The experimental test confirmed the effectiveness of the proposed approach for the construction of the training process with the use of information technology.